Enhancing water and sanitation project performance in a developing economy: Role of governance mechanisms and risk management practices - Benjamin R. Tukamuhabwa; Henry Mutebi; Enoth Akandwanaho; Levi Kabagambe; Ivan Tumukunde (Cogent Business & Management, 2023)
This paper investigates the relationship between governance mechanisms, risk management practices and performance of water and sanitation projects in Uganda. A quantitative cross-sectional survey was conducted with a sample of 66 water and sanitation projects in South-western Uganda. Data were collected using self-administered structured questionnaires and analyzed by using SmartPls Structural Equation modeling. The results revealed positive and significant relationships between the following pairs of variables: contractual governance and project performance, relational governance and risk management practices, and risk management practices and project performance. However, the hitherto hypothesized positive and significant relationships between relational governance and project performance, and contractual governance and risk management practices were not supported. Furthermore, it was established that risk management practices fully mediate in the relationship between relational governance and project performance, whereas they do not mediate between contractual governance and project performance. The fundamental contribution of this article to the project management literature is the confirmation that risk management practices act as mechanisms through which relational governance helps to maximize project performance in the context of water and sanitation projects in a developing country.
Keywords: 650; contractual governance; project performance; relational governance; risk management practices; water and sanitation